2022
DOI: 10.1101/2022.11.29.518321
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Genome-wide circadian gating of a cold temperature response in bread wheat

Abstract: Circadian rhythms coordinate the responses of organisms to their daily fluctuating environments, by establishing a temporal program of gene expression. This schedules aspects of metabolism, physiology, development and behaviour according to the time of day. Circadian regulation in plants is extremely pervasive, and is important because it underpins both productivity and seasonal reproduction. Circadian regulation extends to control of environmental responses through a regulatory mechanism known as circadian ga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
8
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 105 publications
3
8
0
Order By: Relevance
“…3a). The different sets of cold-responsive transcripts at the two time points are consistent with the notion that there is circadian gating of the cold-responsive transcriptome in plants 47 . We compared our cold-responsive transcript set in Col-0 with that of Zhao et al (3 h cold treatment) 48 and found that 42.5% (ZT29) and 13.4% (ZT45) of cold-responsive transcripts were shared between the studies (Extended Data Fig.…”
Section: Sig5 Shapes the Nuclear-encoded Cold-responsive Transcriptomesupporting
confidence: 83%
“…3a). The different sets of cold-responsive transcripts at the two time points are consistent with the notion that there is circadian gating of the cold-responsive transcriptome in plants 47 . We compared our cold-responsive transcript set in Col-0 with that of Zhao et al (3 h cold treatment) 48 and found that 42.5% (ZT29) and 13.4% (ZT45) of cold-responsive transcripts were shared between the studies (Extended Data Fig.…”
Section: Sig5 Shapes the Nuclear-encoded Cold-responsive Transcriptomesupporting
confidence: 83%
“…In sorghum, similar proportions (25-34%) of the heat-responsive transcriptome are gated by the time of day, depending on the genotype (Figure 2C). The genome-wide gating response to temperature is not restricted to heat stress and was also observed under cold stress, as previously reported in Arabidopsis (Blair et al 2019), and recently in wheat (Graham et al 2022).…”
Section: Discussionsupporting
confidence: 81%
“…In terms of heat stress, the response for Sb_GI is similar to what was observed in Arabidopsis where the increased transcript accumulation occurs before (morning) and after (subjective dark) the peak of GI's expression . In a recent study in wheat, TaPRR73 and TaGI are also the two oscillator components that show strong perturbation in response to cold stress resulting in a delay in their peak of expression (Graham et al 2022). These observations suggest that the sensitivity to temperature for some oscillator components may be conserved across species while others may not be.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations